Development of a Black Liquor Electrolyzer for Lignin Extraction. (20th July 2018) - Belo, Inês C.; Oliveira, Raisa Costa Paes; Mateus, Margarida; Bordado, João C.M.; Pinto, Paula; Santos, Diogo M.F.
Abstract : Pulp and paper industry requires developing more sustainable production and improve technologies on biorefinery and bioproduct market areas. Based on these areas, the isolation of lignin from black liquor, obtained by Eucalyptus Globulus, is an important objective. The present study demonstrates that it is possible to recover lignin by electrolysis of the Kraft black liquor in a simple and economic way. This novel black liquor electrolyzer leads to lignin recovery by anodic electrodeposition and cathodic production of hydrogen. Physicochemical characterization of black liquor is made, with the determined values of pH, density, dry solids content and ash content being 13.0, 1111 g cm-3, 16.7 wt.%, and 8.0 wt.% (wet basis) and 40.8 wt.% (dry basis), respectively. The electrolysis experiments are conducted at room temperature on a small-scale laboratory black liquor electrolyzer using Ni plates. ATR-FTIR analysis of the obtained lignin samples is compared with previous literature reports.